2016
DOI: 10.4028/www.scientific.net/msf.852.626
|View full text |Cite
|
Sign up to set email alerts
|

Review of Polymer Surface Modification Method

Abstract: This paper reviewed a variety of methods of polymer surface modification, which mainly includes Solution processing method, Plasma treatment,Surface grafting method,Irradiation treatment and method of Atomic force microscopy probe shock , and the specific polymer material combined with the modification method and its modification mechanism was introduced in detail.Polymer has very extensive application both in chemical fields and in daily life, but due to its poor surface hydrophilicity and wear resistance, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Surface modification technology can be used to make up for this deficiency on the premise of maintaining the original properties of products [ 31 ]. There are mainly surface chemical reaction method, surface grafting method, surface composite method, and other technologies [ 32 ]. Coupling agents are the most commonly used surface modifiers, such as titanate coupling agents, silane coupling agents, and aluminate coupling agents, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification technology can be used to make up for this deficiency on the premise of maintaining the original properties of products [ 31 ]. There are mainly surface chemical reaction method, surface grafting method, surface composite method, and other technologies [ 32 ]. Coupling agents are the most commonly used surface modifiers, such as titanate coupling agents, silane coupling agents, and aluminate coupling agents, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used surface modifications include surface oxidation, plasma treatment, chemical treatment, surface grafting, etc. [6,7] Among them, direct fluorination and plasma treatment are the two most generally used surface modification methods for polymer materials. General and engineering plastics such as PE, PP, PVDF, and PLA have been modified by such two methods for improving wettability, permeability, antifouling properties, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated studies reported several methods for polymers' surface modification, both physical (flame treatment, metal deposition, irradiation techniques and corona-discharge techniques, plasma treatment, etc.) [28][29][30] and chemical (wet chemical methods, surfaces treated with hydrogen peroxide, solution processing method, etc.) [28,30].…”
mentioning
confidence: 99%
“…[28][29][30] and chemical (wet chemical methods, surfaces treated with hydrogen peroxide, solution processing method, etc.) [28,30]. In comparison, the novelty of the proposed method described in this study relies on no modification treatment of the polymeric filaments surface prior to ceramic particles' adhesion.…”
mentioning
confidence: 99%